The understanding of school violence by the social actors of an educational institution - Verônica Borges Kappel; Daniela Tavares Gontijo; Marcelo Medeiros; Luciane Soares Lima (Universidade Federal de Goias, 2015)
This study set out to understand school violence from the perspective of different agents of an educational institution, using qualitative research with data obtained through interviews with 27 actors in a public school and submitted to thematic content analysis. The categories Manifestations of School Violence and School Violence Causes and Consequences emerged from the conversation. Participants highlighted situations in which they portrayed themselves as victims, pointed out manifestations of violence "in," "from," and "towards" school. They related the genesis of violence to relational/social aspects, and the consequences to offenders, victims, and the school itself. The understanding of school violence from the perspective of different stakeholders enabled us to understand the complexity of the phenomenon and the importance of developing actions not only from education professionals, but from multidisciplinary and intrasectoral teams aiming to prevent and work against school violence.